Harvesting time influences fruit removal force, moisture, oil content, free fatty acids and peroxide in the oil of frantoio and manzanilla olive cultivars - Alowaiesh, Bassam; Singh, Zora; Kailis, S. (Southern Cross Publishing, 2016)
Harvesting time at different ripening stages of olive fruit may influence quality attributes of olive oil. Therefore, the effects of five different harvesting times (mid- and late-April, mid- and late-May and mid-June) on fruit removal force, moisture, oil content, free fatty acids and peroxide in the oil of Frantoio and Manzanilla olive cultivars grown in south-western Australia was investigated during 2013 and 2014. The fruit of cv. Manzanilla showed significantly (p = 0.05) higher fruit removal force, moisture content (%) and oil content in dry weight (%) than cv. Frantoio. Furthermore, lowest moisture and oil content were observed in the driest harvest year, in 2014. The free fatty acid content showed significant (p = 0.05) increase and peroxide value decreased with the delay in harvesting from first to fifth periods in both the years, regardless of the cultivars. Overall, harvesting of olive fruit during the early part of winter delivered olive oil content with better quality and climatic conditions such as water stress have negatively influenced the quality attributes of olive oil.